Catalytically Active Species in Copper/DiPPAM‐Catalyzed 1, 6‐Asymmetric Conjugate Addition of Dialkylzinc to Dienones: A Computational Overview. Issue 16 (24th May 2019) - Halbert, Stéphanie; Lauberteaux, Jimmy; Blons, Charlie; de Figueiredo, Renata Marcia; Crévisy, Christophe; Baslé, Olivier; Campagne, Jean‐Marc; Mauduit, Marc; Gérard, Hélène
Abstract: Four different catalytically active species are computationally examined in order to investigate the mechanism of Cu/DiPPAM‐catalyzed 1, 6‐conjugate addition of dialkylzinc to acyclic dienones. A DiPPAM‐bridged Cu(alkyl)‐Zn(acetate) bimetallic complex exhibits the best catalytic activity, which can be associated with the best balance between the stability of the dienone adduct and its activation by copper. The selectivities (regio‐ and enantioselectivity) associated with the retained mechanism are investigated by DFT calculations and successfully compared to experimental data, including the critical influence of the substituents within the dienone on the regioselectivity and the obtained enantioselectivity for the formation of one 1, 6‐adduct. Abstract : Swing the balance : Copper/DiPPAM‐catalyzed 1, 6‐Asymmetric Conjugate Addition (ACA) of dialkylzinc to acyclic dienones pathway is demonstrated to originate from a balance between the activating potential of the two Cu and Zn centers and the stability of the bimetallic complex. The retained mechanism is supported by the experimentally observed regio‐ and enantioselectivities.